Hybrid Engagement: Discourses and Scenarios of Entrepreneurial Journalism - Ruotsalainen, Juho (2018)
Although the challenge posed by social media and the participatory turn concerns culture and values at the very heart of journalism, journalists have been reluctant to adopt participatory values and practices. To encourage audience participation and to offer journalism that is both trustworthy and engaging, journalists of the future may embrace a hybrid practice of journalistic objectivity and audience-centred dialogue. As innovative and experimental actors, entrepreneurial journalism outlets can perform as forerunners of such a culture. By analysing discourses in the “About Us” pages of 41 entrepreneurial journalism outlets, the article examines the emerging journalistic ethos of entrepreneurial journalism and its participatory tendencies. The results show a conception of journalism that is a hybrid of the journalistic ideals of dialogue and objectivity. This kind of hybrid journalism and adjacent “hybrid engagement” can offer an answer to the dual challenge of how to make journalism more participation-friendly while at the same time hold on to the defining values and criteria of journalism. Drawing from futures research, the article concludes by sketching four scenarios of how entrepreneurial journalism and participatory hybrid engagement may develop in the future.